2002
DOI: 10.1097/00130832-200208000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic perspectives on sulfonamide-induced cutaneous drug reactions

Abstract: Despite progress, numerous unresolved issues support the testing of novel hypotheses, the search for additional risk factors, and the need for a global approach, including links between laboratory and clinical paradigms. These issues must be addressed if we are to gain an understanding of the mechanistic bases for these cutaneous drug reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 89 publications
0
13
0
1
Order By: Relevance
“…Since most drug molecules are not highly reactive, bioactivation to reactive species appears to be an essential step in the initiation of immune reactions to these drugs. For sulfonamides in particular, it has been proposed that the formation of arylhydroxylamine metabolites is a determining factor in the CDRs associated with these drugs (Reilly and Ju, 2002;Svensson, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Since most drug molecules are not highly reactive, bioactivation to reactive species appears to be an essential step in the initiation of immune reactions to these drugs. For sulfonamides in particular, it has been proposed that the formation of arylhydroxylamine metabolites is a determining factor in the CDRs associated with these drugs (Reilly and Ju, 2002;Svensson, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Sulfamethoxazole hydroxylamine is a reactive metabolite and may spontaneously form nitrosulfamethoxazole [101]. It has been shown that the nitroso metabolite binds covalently to host proteins, causing direct cellular toxicity, and that this necrotic cell death may provide a 'danger signal' to sensitized T-cells leading to the cascade of immune response and cytokine release manifesting as drug hypersensitivity [102].…”
Section: Drugs For Opportunistic Infectionsmentioning
confidence: 99%
“…Many of these cutaneous drug reactions are observed 7 days after drug initiation, suggesting idiosyncratic, delayed hypersensitivity reactions. 8 Risk factors include higher CD4 1 T-cell count >20 3 10 6 cells/L, 9 CD4:CD8 ratio <0.10, treatment for less than 14 days, 10 and possibly a slow acetylation phenotype. 11 Male sex, higher CD4 1 T-cell percentage, a history of syphilis, and a higher total protein are also associated with cutaneous reactions to TMP-SMX.…”
Section: Hypersensitivity To Trimethoprim-sulfamethoxazolementioning
confidence: 99%
“…Lymphocytes from immunocompetent patients with a history of TMP-SMX hypersensitivity display higher sulfamethoxazole cytotoxicity than those of control subjects. 8,16 Desensitization Several desensitization protocols have been developed for use in both adults and children with TMP-SMX hypersensitivity. Drug desensitization is defined as the conversion of a state of drug hypersensitivity to a nonreactive state by the cautious introduction of increasing amounts of antigen at regular time intervals over a relatively short period (4-6 hours).…”
Section: Pathogenesismentioning
confidence: 99%